(untitled) - G J Blower (London, 1995)
The book is well-etablished as an essential guide to understanding of plumbing principles and process. It includes new material on health and safety, sanitary plumbing and sheet metal weatherings. This book is a key course text for NVQ mechanical engineering services: plumbing level 2. It is also useful supplementary reading for NVQ level 2 gas services installation and maintenance, mechanical engineering services; heating and ventilation, plumbing craft and heating and ventilation fitting craft
Keywords: environmental engineering,mechanical engineering services,plumbing